Increasing Vocabulary Mastery of The Seventh Grade Students of SMP Negeri 3 Parepare Through Mind Mapping Technique - Sulfina; Patahuddin (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2020)
Vocabulary is one components of language. Vocabulary is one of the most important things to make our communication be fluent. One of component that links the listening, speaking, reading is vocabulary.. The objective of the research is to find out whether or not the use of riddle can improve the vocabulary of the seventh grade students of SMP Negeri 3 Parepare. The research applied quasi-experimental method with two classes, experimental class and control class. The population of this research was the seventh grade students of SMP Negeri 3 Parepare in academic year 2017/2018. The total number of population were 278 students and two classes of nine classes taken as sample by using cluster random sampling. The total number instrument of the pre-test and post-test of this research were 20 number which divide into 10 match the words, 5 multiple choice and 5 fill in the blank. The result of data analysis shows that the students vocabulary improved. It was showed by the mean score of pre-test was 6,5 and post-test 85.83. it shows that the use mind mapping can improve the students vocabulary of the seventh grade of SMP Negeri 3 Parepare.. After analyzing the data by using the test formula, the result of t-test value in post-test was 0,665 and t-table value was 2.000. It means that t-test value 0,665 was higher than t-table value 2.000. Those indicates that H₀ was rejected and H₁ was accepted and the students who were taught by using riddle is better than the students who were taught by using text book.